Pembiasaan Membaca Asmaul Husna Untuk Menjaga Potensi Aqidah Pada Anak - Syaifur Rohman (DIMAR: Jurnal Pendidikan Islam, 2020)
Humans are created in the world with the potential in themselves as provisions for living in the world and preparing for the afterlife. Humans are given the task not only as a caliph who controls life in the world, but at the same time they are given the task of being a servant who must worship Allah SWT. not only social and individual beings but also religious beings who have theological aspects in living life in the world. The potential in every human being born will continue to grow along with the physical development of their bodies. Correct guidance will make the spiritual potential in children develop optimally. One way to optimize spiritual potential in children is to memorize Asmaul Husna as early as possible. Asmaul Husna or the beautiful names of Allah SWT is a means for every human being to get closer to the creator. With Asmaul Husna Allah SWT promises various kinds of goodness both in this world and in the hereafter. By looking at the aspects of development in children, the habit of reciting Asmaul Husna will have a positive impact on the spiritual development of children.